Immunosensing of prostate cancer in human plasma samples using immobilization of antibody on the surface of mesoporous silica-modified silver nanoparticles and its immunocomplex with prostate-specific antigen. Issue 48 (28th November 2019) - Farshchi, Fatemeh; Hasanzadeh, Mohammad; Solhi, Elham
Abstract : An innovative screening method for the early stage diagnosis of prostate cancer in human plasma samples is proposed in this study. Abstract : An innovative screening method for the early stage diagnosis of prostate cancer in human plasma samples is proposed in this study. For this purpose, an immunoassay based on the immobilization of PSA antibody on mesoporous silica–silver nanoparticles (MSNPs–AgNPs) was successfully designed and developed for the detection of the PSA biomarker in human plasma samples. The SiO2 –AgNPs provide a large surface area for the effective immobilization of PSA antibody; also, this system ascertains the bioactivity and stability of immobilized PSA antigens. Field emission scanning electron microscopy (FE-SEM) was employed to monitor the sensor fabrication. The engineered immunosensor was used for the detection of PSA using differential pulse voltammetry (DPV) and square wave voltammetry (SWV) techniques. The proposed interface leads to enhancement of the accessible surface area for immobilizing a high amount of anti-PSA antibody, increasing the electrical conductivity and enhancing the stability, catalytic properties and biocompatibility. Under the optimized conditions, the low limit of quantitation (LLOQ) for the proposed immunosensor was recorded as 1 ng mL −1, and this evaluation was performed in a highly linear range of 0.1–0.001 μg L −1 . The proposed immunoassay was successfully applied for monitoring PSA in unprocessed human plasma samples.